Autoria múltipla como fator constitutivo da comunidade científica em medicina tropical, no Brasil - Claudio Omar Iahnke Nunes (1990)
The investigation focussed on multiple authorship among researchers who presented papers at congresses sponsored by the Brazilian Society of Tropical Medicine, from 1967 to 1989. This study aimed at developing an appropriate method to identify contemporaneous scientific communities, by utilizing Thomas S. KUHNs theoretical assumptions, especially those concerning the concept of consensus among scientists. An analysis of 5101 papers was carried out through successive segmentations of collected data. The first partition allowed for the identification, out of 6882 authors, of those 378 authors who had presented ten or more papers, typifying them as productive authors. After a second segmentation, this last group (378 authors) was split into three sub-groups: 159 authors who behaved as anchors; 112 authors who acted as gatekeepers; and 160 authors who were only typified as prolific authors. Out of the 159 anchor authors, 27 behaved as such in at least three congresses, and were considered as the amalgamating nucleus within the Brazilian Society of Tropical Medicine. This nucleus was submitted to a final segmentation, and out of the 27 authors, four authors were characterized as community leaders. The basic supporting concept for the analysis was that of convergence among authors and among groups. The findings constituted empirical evidence that increasing proportions of multiple authorship, verified in the period considered, established the indispensable community basis for the emergence of consensus, such as proposed by Thomas S. KUHN.